What Are the Indications for Spinal Fusion Surgery in Scheuermann Kyphosis?. Issue 5 (May 2019) - Polly, David W.; Ledonio, Charles G.T.; Diamond, Beverly; Labelle, Hubert; Sucato, Daniel J.; Hresko, M. Timothy; Emans, John B.; Vitale, Michael G.; Erickson, Mark A.; Larson, A. Noelle
Abstract : Background: Surgical indications for Scheuermann kyphosis are variable. We sought to evaluate the characteristics of patients undergoing operative versus nonoperative treatment of Scheuermann kyphosis to better understand current practices and the factors which contribute to the decision for surgical management. Methods: Multicenter prospective cohort study. We evaluated consecutive patients presenting with Scheuermann kyphosis. Patients underwent either surgical or nonoperative management according to surgeon and patient discretion. Preoperative patient-reported outcome measures (Scoliosis Research Society and Spinal Appearance Questionnaire scores), demographics, and radiographic characteristics were assessed. Results: Overall, 150 patients with Scheuermann kyphosis were enrolled, with 77 choosing nonoperative treatment and 73 treated operatively. Compared with the nonoperative cohort, patients treated operatively were older (16.3±2.0 vs. 15.1±2.2, P =0.0004), and had higher body mass index (26.3±7.2 vs. 22.7±6.5, P =0.003), had greater T2-T12 kyphosis (71±14 degrees vs. 61±12 degrees, P <0.001), increased pelvic incidence (46 vs. 41 degrees, P =0.03) and pelvic tilt (10 vs. 3 degrees, P =0.03). There was no detected difference in maximal sagittal Cobb angle in the operative versus nonoperative patients (73±11 vs. 70±12 degrees, P =0.11). Functionally, the operative patients had worse Scoliosis Research Society pain scores (3.7±0.9 vs. 4.1±0.7, P =0.0027) and appearance scores (2.9±0.7 vs. 3.4±0.8, P <0.0001). Conclusions: Patients undergoing surgical management of Scheuermann disease were more likely to have large body mass index and worse pain scores. Other factors beyond radiographic measurement likely contribute to the decision for surgical management of Scheuermann kyphosis. Level of Evidence: Level II.